INFLUENCE OF NARRATIVES IN THE CONSTRUCTION OF TOURIST IMAGINARIES ABOUT CABO DE LA VELA. - Aponte Aarón, María Laura
The present research aims to analyze the influence of narratives in the construction of tourist imaginaries of Cabo de La Vela, using the mixed approach using interviews, surveys and non-participating observation as the main instruments, finding that travel agencies, visitors, local Wayuu entrepreneurs and other entities that create narratives of this place, induce other tourists to seek mainly sun and beach activities, and with less force the culture. Therefore, it can be concluded that the tourist imaginary of Cabo de a Vela is strongly influenced by the photographs, images, videos and comments that most tourism actors make about the beauty of the landscape, above the cosmogonic meaning of the place.